Dynamic pricing of ancillary services based on passenger choice behavior. (July 2021) - Zhao, Guihong; Cui, Yue; Cheng, Shaoyu
Abstract: Based on passenger choice behavior, a dynamic pricing mechanism of ancillary services has been brought up for analysis in this paper. With the analysis of the passenger choice behavior of ancillary services, this study (1) analyzed the pricing of ancillary services from airlines' websites, (2) launched a survey to investigate passengers' characteristics and preferences, (3) applied the binary logistic model to analyze passenger choice of ancillary services, and integrated into the dynamic pricing model of ancillary services. The optimal prices can be obtained at the maximum of the revenue. Based on the historical data of a Chinese domestic flight, the optimal prices of ancillary services for different types of passengers can be obtained at the maximum revenue of ancillary services, with a 74.4% increase of revenue. This paper not only created a general pricing model for improving the ancillary revenue but also provided theoretical support for ancillary pricing. The model with enough data can be dynamically applied to various flights and ancillary services. Highlights: Background and Significance: The income from ancillary services has become a very important source of airline revenue. To follow the market trend and better meet the needs of passengers, this paper intends to discuss the choice behavior of passengers for different ancillary services, and finally proposes a dynamic pricing strategy that maximizes the flight revenue of ancillary services. Originality and Novelties: This paper put forward a dynamic pricing mechanism of ancillary services based on passenger choice behaviors. The model combined subjective data from passenger survey and objective data from actual flight data, reaching the best price point of balancing customer satisfaction and revenue maximization. Extensive Interests: The model can help increase flight revenue and supplement the revenue management system of ancillary services: airlines can predict passenger choice behavior and build a multi-period dynamic pricing system based on passenger classification.